La resilienza in psichiatria: un’ipotesi di definizione - Migliorini, Vanina; Fazio, Cinzia (Il sogno della farfalla, 2018)
The term resilience, which is derived from the mechanics of materials, has been steadily used in several other scientific domains, including psychiatry. In psychiatry, resilience refers to individuals’ capability to face traumatic events positively. Starting from the idea of resilience as individuals’ capability to face adversities and traumatic events in their life without severe crisis or internal fragmentation, studies have gone as far as considering resilience as the promoting factor of individuals’ wellbeing and happiness. However, as it has been underlined by the authors, on the one hand research on resilience is associated with the idea of an innate capability human beings have to resist adversities, and, on the other, it does not gather the term’s most genuine sense. Hence, research appears to be confused about the use of the term and when it comes to highlight the factors that determine the onset of resilience itself. The point of view proposed by the authors is based on Human Birth Theory by Massimo Fagioli, and finds the traumatic factors in events that cannot be perceived directly, meaning in interhuman relationships that are based on the lack of affectivity. The actual «protective factor» is vitality that, as it is derived from the physiology of human birth and characterizes all human beings, provides human beings with sensibility and an internal movement as capability to react to the lack of affectivity. As such, it is the basis for actual transformative potential.